Costs and Resource Utilization for Diagnosis and Treatment During the Initial Year in a European Inflammatory Bowel Disease Inception Cohort: An ECCO-EpiCom Study. Issue 1 (January 2015) - Burisch, Johan; Vardi, Hillel; Pedersen, Natalia; Brinar, Marko; Cukovic-Cavka, Silvja; Kaimakliotis, Ioannis; Duricova, Dana; Bortlik, Martin; Shonová, Olga; Vind, Ida; Avnstrøm, Søren; Thorsgaard, Niels; et al.
Abstract : Background: No direct comparison of health care cost in patients with inflammatory bowel disease across the European continent exists. The aim of this study was to assess the costs of investigations and treatment for diagnostics and during the first year after diagnosis in Europe. Methods: The EpiCom cohort is a prospective population-based inception cohort of unselected inflammatory bowel disease patients from 31 Western and Eastern European centers. Patients were followed every third month from diagnosis, and clinical data regarding treatment and investigations were collected. Costs were calculated in euros ([Euro sign]) using the Danish Health Costs Register. Results: One thousand three hundred sixty-seven patients were followed, 710 with ulcerative colitis, 509 with Crohn's disease, and 148 with inflammatory bowel disease unclassified. Total expenditure for the cohort was [Euro sign]5, 408, 174 (investigations: [Euro sign]2, 042, 990 [38%], surgery: [Euro sign]1, 427, 648 [26%], biologicals: [Euro sign]781, 089 [14%], and standard treatment: [Euro sign]1, 156, 520 [22%)]). Mean crude expenditure per patient in Western Europe (Eastern Europe) with Crohn's disease: investigations [Euro sign]1803 ([Euro sign]2160) ( P = 0.44), surgery [Euro sign]11, 489 ([Euro sign]13, 973) ( P = 0.14), standard treatment [Euro sign]1027 ([Euro sign]824) ( P = 0.51), and biologicals [Euro sign]7376 ([Euro sign]8307) ( P = 0.31). Mean crude expenditure per patient in Western Europe (Eastern Europe) with ulcerative colitis: investigations [Euro sign]1189 ([Euro sign]1518) ( P < 0.01), surgery [Euro sign]18, 414 ([Euro sign]12, 395) ( P = 0.18), standard treatment [Euro sign]896 ([Euro sign]798) ( P < 0.05), and biologicals [Euro sign]5681 ([Euro sign]72) ( P = 0.51). Conclusions: In this population-based unselected cohort, costs during the first year of disease were mainly incurred by investigative procedures and surgeries. However, biologicals accounted for >15% of costs. Long-term follow-up of the cohort is needed to assess the cost-effectiveness of biological agents. Abstract : Article first published online 1 December 2014.